Effect of a storytelling intervention on the retention of serodiscordant couples in ART/PrEP services at antenatal clinic in Namacurra province in Zambézia, Mozambique - Carolyn M Audet; Erin Graves; Almiro M Emílio; Ariano Matino; Paula Paulo; Arifo M Aboobacar; Carlota L Fonseca; Sara Van Rompaey; Caroline De Schacht (My University, 2021)
Background: Sub-Saharan Africa reported 550,000 new HIV infections among women in 2018. Pregnancy and the postpartum period are associated with an increased risk of HIV acquisition (adjusted risk ratio [RR]: 2.8 during pregnancy and 4.0 in postpartum period vs. non-pregnant or postpartum women, respectively). Acquisition of HIV during pregnancy and breastfeeding increases risk of mother to child transmission. We propose to test the impact of a peer-delivered oral storytelling intervention to increase retention in, and adherence to, pre-exposure prophylaxis (PrEP)/combination antiretroviral treatment (ART) among expectant couples. Design: We propose a randomized controlled trial (RCT) (35 intervention and 35 control couples) at a health facility where 11% of expectant couples were in serodiscordant relationships in 2018. Couples randomized to the storytelling arm will be visited by a two community volunteers and who successfully adhered to PrEP/ART during a recent pregnancy. This expert couple will orate to participating couples three stories (at 1, 3 and 5 weeks after study enrollment) designed to empower, educate, and establish "ideal" interpersonal communication strategies within couples/families, and support adherence practices among participants. The primary outcome among HIV-uninfected women will be adherence to PrEP at 3 months. Conclusions: PrEP among at-risk pregnant women must be implemented so that high levels of adherence and retention are achievable for them and their partners. We will test our storytelling intervention to identify an optimal strategy for PrEP education and family engagement in a region with high HIV prevalence. Our results will have an impact by effectively engaging serodiscordant couples in prevention/treatment during pregnancy and beyond.
Keywords: Antenatal care; Male-engagement; Mother-to-child transmission of HIV; PrEP uptake and adherence; Storytelling.